Increasing Student Understanding of The Dynamics and Challenges of Indonesian Democracy Based on Literature Review Through Mass Media - Iksadar Iksadar; Dikdik Baehaqi Arief; Mukhamad Murdiono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This results aims to determine students' understanding of the learning material provided. This aims to highlight the significance of mass media and digital literacy in enhancing students' knowledge and skills. The type of research employed in this result is descriptive, with a qualitative approach. Data were collected by observation, interview, and documentation techniques. Checking the validity of the data using triangulation techniques. Data analysis techniques include data reduction, data presentation, and verification. The results indicate that key factors for students to understand the dynamics and challenges of Indonesian democracy include awareness of the importance of democracy, the ability to learn and adapt, openness to societal problems, practical communication skills, and the courage to fight for truth and justice. Therefore, the mass media can serve as a source of literature that enhances student understanding.